2020
DOI: 10.1093/ee/nvaa098
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Gut Bacterial Communities of Ips typographus (Coleoptera: Curculionidae) Induced by Enantiomer-Specific α-Pinene

Abstract: The spruce bark beetle (Ips typographus L.) is a destructive pest of Eurasian spruce forests. Although the gut bacteria of this insect are considered to play important roles in its lifecycle, the relationship between I. typographus and its gut bacterial community is poorly characterized. In this study, 16S rRNA gene sequencing was used to determine gut bacterial community composition across successive I. typographus life stages. Responses of the gut bacteria to α-pinene enantiomers were also explored. Ips typo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 54 publications
2
12
1
Order By: Relevance
“…Apart from Wolbachia (Proteobacteria), the remaining top 10 most abundant bacterial genera detected in M. velezangeli include members of Phylum Firmicutes (5.2% overall abundance), such as Romboutsia, Clostridium, Allobaculum, Blautia, Eubacterium_g23, Sporobacter, Dorea and Faecalibacterium, as well as the Proteobacteria genera Paracoccus, Methylobacterium and the Chlorobi genus Ignavibacterium. Members of these Firmicutes genera have been previously found in the alimentary canals of other arthropods [58][59][60][61][62][63]. In our study, Romboutsia (1.75%) (Firmicutes: Peptostreptococcaceae) was the second most abundant bacterial genus across all samples.…”
Section: Discussionsupporting
confidence: 57%
“…Apart from Wolbachia (Proteobacteria), the remaining top 10 most abundant bacterial genera detected in M. velezangeli include members of Phylum Firmicutes (5.2% overall abundance), such as Romboutsia, Clostridium, Allobaculum, Blautia, Eubacterium_g23, Sporobacter, Dorea and Faecalibacterium, as well as the Proteobacteria genera Paracoccus, Methylobacterium and the Chlorobi genus Ignavibacterium. Members of these Firmicutes genera have been previously found in the alimentary canals of other arthropods [58][59][60][61][62][63]. In our study, Romboutsia (1.75%) (Firmicutes: Peptostreptococcaceae) was the second most abundant bacterial genus across all samples.…”
Section: Discussionsupporting
confidence: 57%
“…Cnaphalocrocis medinalis (Pyralidae) (Y. J. Yang et al, 2020), Adelphocoris suturalis (Miridae) (Xue et al, 2021), Ips typographus (Scolytidae) (Fang et al, 2020), Tuta absoluta (Meyrick) (H. Wang et al, 2022). Proteobacteria and Firmicutes were widely present in different insect taxa and in high abundances which is expected as they was reported to be associated with host environmental adaptation, digestion, nutrient supply, and energy metabolism (Cao et al, 2021;B.…”
Section: Discussionmentioning
confidence: 95%
“…Our results agree with that of (Schloss et al, 2006) who identified that Proteobacteria and Firmicutes are two abundant bacteria phylum in A. glabripennies . Similar results were found across different taxa of insect, such as Monochamus alternatus and Psacothea hilaris (Cerambycidae) (Kim et al, 2017), Rhynchophorus ferrugin (Muhammad et al, 2017), Popillia japonica (Scarabaeidae) (Chouaia et al, 2019), Cnaphalocrocis medinalis (Pyralidae) (Y. J. Yang et al, 2020), Adelphocoris suturalis (Miridae) (Xue et al, 2021), Ips typographus (Scolytidae) (Fang et al, 2020), Tuta absoluta (Meyrick) (H. Wang et al, 2022). Proteobacteria and Firmicutes were widely present in different insect taxa and in high abundances which is expected as they was reported to be associated with host environmental adaptation, digestion, nutrient supply, and energy metabolism (Cao et al, 2021; B. S. Chen et al, 2016; Fonknechten et al, 2010; Martinez et al, 2019; Mohammed et al, 2018; Suen et al, 2010; Yun et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies were based on pooled I. typographus guts from one restricted geographic area (Chakraborty et al 2020; Fang et al 2020; Yu et al 2022; Veselská et al 2023), our approach allowed a fine-scale analysis of several European populations on a single individual level. Our analysis revealed that the genera Erwinia and Pseudoxanthomonas which were previously described in I. typographus in the Czech Republic and in China (Chakraborty et al 2020; Fang et al 2020; Yu et al 2022) can be considered the core bacterial community being present in all individuals ( Erwinia ) and in 98.44% of the individuals ( Pseudoxanthomonas ). The omnipresence of these two genera across most individuals from different populations across Europe suggests that these bacteria might be essential for I. typographus to successfully colonize trees and utilize the subcortical material as a food source.…”
Section: Discussionmentioning
confidence: 99%
“…Although our understanding of the bacterial community structure of I. typographus has increased in recent years (Chakraborty et al 2020; 2023; Fang et al 2020; Yu et al 2022; Veselská et al 2023), surprisingly little knowledge exists about the taxonomic composition and diversity across different geographic regions, epidemiological and overwintering phases. Here, we first describe the taxonomic composition and core-microbiome of I. typographus by characterizing the bacterial communities of different populations from a large area of Europe, including the four major refugial areas, in the Apennines, the Dinaric Alps on the Balkan Peninsula, the Carpathian Mountains and in the Russian plain (Tollefsrud et al 2009).…”
Section: Introductionmentioning
confidence: 99%